2003
DOI: 10.1152/japplphysiol.00890.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human pulmonary vascular response to 4 h of hypercapnia and hypocapnia measured using Doppler echocardiography

Abstract: . Human pulmonary vascular response to 4 h of hypercapnia and hypocapnia measured using Doppler echocardiography. J Appl Physiol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
104
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 20 publications
7
104
0
4
Order By: Relevance
“…However, there were more severe patients undergoing RA, indicated by both haemodynamics and the fact that significantly more patients on specific PAH therapy received RA than GA. The use of GA may increase PVR through several mechanisms, including increased sympathetic stimulation during airway instrumentation on laryngoscopy [39], effects of volatile agents [40], high airway plateau pressure due to the effects of positive-pressure mechanical ventilation [12,13], hypoxia [15] and hypercapnia [16]. The present data suggested that more complications occurred in those with higher PET,CO 2 and peak airway pressure, although many confounding factors may affect these values.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, there were more severe patients undergoing RA, indicated by both haemodynamics and the fact that significantly more patients on specific PAH therapy received RA than GA. The use of GA may increase PVR through several mechanisms, including increased sympathetic stimulation during airway instrumentation on laryngoscopy [39], effects of volatile agents [40], high airway plateau pressure due to the effects of positive-pressure mechanical ventilation [12,13], hypoxia [15] and hypercapnia [16]. The present data suggested that more complications occurred in those with higher PET,CO 2 and peak airway pressure, although many confounding factors may affect these values.…”
Section: Discussionmentioning
confidence: 61%
“…A common mode of death appears to be minor stimulation resulting in tachycardia or increased PVR, followed by refractory hypotension, hypoxia and ultimately cardiovascular collapse [12,13] due to a downwards spiral of worsening right ventricular function [14]. Perioperative increases in PVR may be precipitated by hypoxia [15], hypercapnia [16], high airway plateau pressure due to the effects of positive-pressure mechanical ventilation [17] and atelectasis or may follow acute pulmonary embolism [18]. Such PH complications, including death, may occur up to 1 week post-operatively [19,20], or even later, reported following delivery by Caesarean section [21,22].…”
mentioning
confidence: 99%
“…Moderate CO 2 elevations predictably increase pulmonary vascular resistance and pulmonary artery pressure, but also increase right ventricular performance and cardiac index secondary to sympathetic stimulation. 39,40 Caution is required in patients with significant right ventricular dysfunction or depressed adrenergic state, particularly with a more pronounced hypercapnia (PaCO 2 [70 mmHg). PaCO 2 levels as high as 70-135 mmHg have been observed during OLV and were shown to be associated with ventricular arrhythmias, oxygenation difficulties, and frequently the need for inotropic support.…”
Section: Recruitmentmentioning
confidence: 99%
“…Low tidal volumes (4-6 mL/kg IBW) have shown to reduce the risk of lung injury after thoracotomy [38] as well as permissive hypercapnia, which is thought to improve oxygenation by increasing hypoxic pulmonary vasoconstriction and, consequently, reducing shunt volume [39] .…”
Section: Avoiding Ventilation Associated Lung Injurymentioning
confidence: 99%